1995
DOI: 10.1159/000217140
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Methods for Deep Vein Thrombosis

Abstract: Clinical diagnosis of deep vein thrombosis (DVT) is unreliable, and treatment should not be undertaken without objective confirmation. The traditional ‘gold standard’ for the diagnosis of DVT has been venography, but ultrasonic imaging has now replaced venography as the new diagnostic standard in many hospitals. A variety of noninvasive physiologic tests are also useful in selected circumstances. These include plethysmography, Doppler flow studies, radioisotope tests, thermography and peripheral blood tests wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 60 publications
(75 reference statements)
0
17
0
1
Order By: Relevance
“…For medical and physiological monitoring, DITI has been used as a non-invasive diagnostic technique to detect infrared emissions and create thermal maps displaying temperature distributions. These thermal maps are used when diagnosing breast cancer (Head and Elliott 2002) and can also be instrumental in diagnosing vascular occlusions and deep venous thrombosis (Wheeler and Anderson 1995). While the temperature of the skin is generally about 58C cooler than the body core, since heat is often dissipated through the skin by evaporation and other methods to balance internal and external temperature (Adams et al 1980), it is possible to detect infrared emissions from the skin and create a thermal map of temperature distributions by remote sensing (Purohit et al 1985).…”
mentioning
confidence: 99%
“…For medical and physiological monitoring, DITI has been used as a non-invasive diagnostic technique to detect infrared emissions and create thermal maps displaying temperature distributions. These thermal maps are used when diagnosing breast cancer (Head and Elliott 2002) and can also be instrumental in diagnosing vascular occlusions and deep venous thrombosis (Wheeler and Anderson 1995). While the temperature of the skin is generally about 58C cooler than the body core, since heat is often dissipated through the skin by evaporation and other methods to balance internal and external temperature (Adams et al 1980), it is possible to detect infrared emissions from the skin and create a thermal map of temperature distributions by remote sensing (Purohit et al 1985).…”
mentioning
confidence: 99%
“…In a recent study, color Doppler ultrasound showed poor sensitivity (38%) and a poor positive predictive value (26%) for the detection of proximal DVT in high-risk patients without clinical symptoms (22). Besides the higher costs of ultrasound as well as the requirement for a skilled operator, the procedural time may be long and therefore plethysmographic tests may be more suitable for routine use (23). Since we observed a high rate of abnormal pulmonary perfusion scans without the presence of any clinical symptoms for PE these patients belong to a low-probability group.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it was not very sensitive at picking up thrombi in the groin or pelvis. The test was mainly used as a study tool but went out of favour because of the infection risk associated with injecting blood products [ 110 ].…”
Section: Fibrinogen Uptake Testmentioning
confidence: 99%